2018
DOI: 10.1161/jaha.117.008057
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Arch Width and Cardiovascular Disease in Men and Women in the Community

Abstract: BackgroundWe sought to determine whether increased aortic arch width (AAW) adds to standard Framingham risk factors and coronary artery calcium (CAC) for prediction of incident adverse cardiovascular disease (CVD) events in community‐dwelling adults.Methods and ResultsA total of 3026 Framingham Heart Study Offspring and Third Generation cohort participants underwent noncontrast multidetector computed tomography from 2002 to 2005 to quantify CAC. We measured AAW as the distance between the centroids of the asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…First, we did not quantify the inter-observer reproducibility, but the aortic boundaries could be delineated clearly on the CT images. Thus, a significant variability was not expected as has been shown before (11). Second, AAW was measured on axial 2D images and not on 3D reconstructions, which might lead to underestimation or overestimation of the AAW in cases of aortic tortuosity.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…First, we did not quantify the inter-observer reproducibility, but the aortic boundaries could be delineated clearly on the CT images. Thus, a significant variability was not expected as has been shown before (11). Second, AAW was measured on axial 2D images and not on 3D reconstructions, which might lead to underestimation or overestimation of the AAW in cases of aortic tortuosity.…”
Section: Discussionmentioning
confidence: 85%
“…Lee et al (5) concluded in their study that unfolding of the aorta as measured by AAW on non-contrast CT was positively associated with the age, BSA, hypertension, and coronary artery calcium 4) reported that larger AAW was significantly correlated with left ventricle impaired function and remodeling as well as higher coronary artery calcification. Chuang et al (11) suggested, according to their study results, that AAW helped in CVD risk stratification and added a predictive value for adverse CVD events. In the present study, CAD severity degree, as defined by GS, was significantly positively associated with the patient's age and AUI but not with the patient's sex.…”
Section: Discussionmentioning
confidence: 99%
“…Another novel morphological parameter identified in our study was aortic width, which acted as a supplementary illustration to the spatial geometry of the aorta. Previous studies revealed a subtle association between aortic width and adverse cerebrocardiovascular events among communitydwelling adults (Chuang et al, 2018), probably due to the fact that spatial tortuosity may augment the severity and distribution of flow disturbances (Xie et al, 2013;Li et al, 2019). In order to be widely applicable in clinical practice, those pre-identified morphological risk factors need to be integrated into a risk stratification algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic arch width, commonly defined as the distance between the ascending and descending aorta at the level of the pulmonary artery bifurcation, increases with age, 16 , 94 showed independent predictive values for cardiovascular events in the general population and its evaluation from cine MRI showed excellent reproducibility. 95 Along with curvature, a geometrical description of local bending computed from local spatial derivatives of the centerline, they may become an important parameter to assess local arterial aging. 16 , 94 Beyond geometrical descriptors, comprehensive hemodynamic data such as those obtained by 4D flow MRI informed about the impact of aging on specific flow features, 21 such as wall shear stress, which drives aortic remodeling and wall degeneration.…”
Section: Other Possible Biomarkersmentioning
confidence: 99%